Identification of Everyday Sounds Affects Their Pleasantness - Heller, Laurie M.; Smith, Jessica M. (Frontiers in Psychology, 2022)
This study examines the role of source identification in the emotional response to everyday sounds. Although it is widely acknowledged that sound identification modulates the unpleasantness of sounds, this assumption is based on sparse evidence on a select few sounds. We gathered more robust evidence by having listeners judge the causal properties of sounds, such as actions, materials, and causal agents. Participants also identified and rated the pleasantness of the sounds. We included sounds from a variety of emotional categories, such as Neutral, Misophonic, Unpleasant, and Pleasant. The Misophonic category consists of everyday sounds that are uniquely distressing to a subset of listeners who suffer from Misophonia. Sounds from different emotional categories were paired together based on similar causal properties. This enabled us to test the prediction that a sound’s pleasantness should increase or decrease if it is misheard as being in a more or less pleasant emotional category, respectively. Furthermore, we were able to induce more misidentifications by imposing spectral degradation in the form of envelope vocoding. Several instances of misidentification were obtained, all of which showed pleasantness changes that agreed with our predictions.